Cyber Security in Digitized E-Governance: Evaluating Indian IT Act 2000 (As Amended in2008) in Context - Dey, Alice; Dey, Sadhan Kumar (International Journal of Mass Communication, 2023)
Digital technology and Cyber-based database management system in Indian e-governance has brought about dramatic changes in the mode of operations in all governmental business transactions in India. Government organizations and Government professionals need to depend upon the electronic media and computer-generated e-records for e - governance. Information Technology poses new and complex ethical, legal and extra- legal threats to e-governance. This e-governance inter alia involves the question of security against abuses and misuses of Information Technology The situation demands a fresh look into the problem of Cyber Security in e-governance . Information stored in electronic form is cheaper, faster and easier to store, retrieve and to access than traditional paper –based government records. But the question remains: How far these electronic e-governance records are maintainable in Indian court of law under IT Act 2000 (as amended in 2008)? Government is aware of the advantages of e-records but is reluctant to conduct or conclude business transactions in the electronic form due to lack of legal framework in India. Globalized technological changes have created a new global economy powered by technology, fuelled by information and driven by the concept of e-governance of the ‘government’. The present paper will analyze the challenge of digitized government and will seek answer to the question mentioned above related to Cyber Security in IT- enabled environment of digitized government of India. IT Act 2000 (as amended in 2008) will be critically analyzed and evaluated to find out its efficacy and limitations in ensuring security of e-governance of India.